AN OUTDOOR LEARNING APPROACH THROUGH THE USE OF CULTURAL HERITAGE SITES TO IMPROVE STUDENTS’ CULTURAL LITERACY - Ayu, Wulan Agustri; Sugeng Harianto; Nugroho Hari Purnomo; I Gusti Agung Adi Wira Buwana (Universitas Negeri Surabaya, 2025)
This study develops an outdoor learning model utilizing cultural heritage sites to enhance students’ cultural literacy. Several nearby sites such as Pamotan Temple 1 and 2, Lemah Duwur Temple, Pari Temple, and Sumur Temple serve as contextual learning resources. Using a design- based research (DBR) approach, the development process includes analysis, design, and evaluation stages. Data were collected through literature review, expert review, and model validation. The resulting model comprises five core components: impact, syntax, teacher roles, support systems, and learning principles. The model is deemed feasible for implementation and relevant to promoting meaningful, contextual cultural learning.